Технологія налагодження співпраці венчурного інвестора та інноваційного підприємства - Мельник, О. Г.; Адамів, М. Є.; Омелянчук, А. Б.; Melnyk, O. G.; Adamiv, M. Y.; Omelianchuk, A. B. (Видавництво Львівської політехніки, 2021)
Обґрунтовано актуальність залучення венчурних інвестицій для розвитку інноваційної діяльності підприємств. Ретельно досліджено сучасний стан і тенденції розвитку венчурного інвестування в Україні. Ідентифіковано проблеми та перешкоди для функціонування вітчизняного венчурного бізнесу. На підставі отриманих результатів дослідження та врахування кращого іноземного досвіду сформовано комплексну поетапну технологію залучення венчурного капіталу інноваційними підприємствами. Обґрунтовано специфіку ведення переговорів та укладання угоди венчурного інвестування між венчурним інвестором та інноваційним підприємством.

In the article it is established that today in Ukraine the development of venture investment of innovative enterprises is at an early stage and is characterized by a number of problems. The dynamics of venture capital in Ukraine shows that their number and capitalization have been growing rapidly during the research period 2011–2019, and this growth continued even after the crisis. It is worth noting that venture investments in Ukraine are made in points, in particular they are more concentrated in Kyiv and Lviv. The largest share of venture capital is international capital. The most attractive sectors for venture investment in Ukraine are software, online services and IT equipment. According to the results of studying domestic and foreign experience of venture investment, a number of obstacles in the development of venture business in Ukraine have been identified: instability of the external environment; underdeveloped venture infrastructure; low level of efficiency of regulation of venture investment at the legislative level; low liquidity of venture capital due to the low level of stock market development; the predominance of foreign origin of venture capital and the shortage of domestic investment resources; underestimation of the role of small and medium business in the innovative development of the economy; low level of quality of venture fund management; weak information support and insufficient transparency of venture business. Based on the best foreign experience of venture business and existing problems in the field of venture investment in Ukraine, a technology for attracting venture capital at the stage of negotiating and concluding a venture investment agreement has been developed. The proposed technology will provide an opportunity to form a unified and clear basis for concluding a venture investment agreement between foreign venture investors and domestic innovative enterprises. The use of the proposed technology in the domestic practice of venture investment will increase the attractiveness of cooperation with Ukrainian innovation organizations in the eyes of foreign investors. This, in turn, will intensify the attraction of foreign investment in the development of the innovative sector of the national economy.
Technology of establishing cooperation between venture investor and innovative enterprise
Keywords: венчурні інвестиції; венчурні фонди; венчурний капітал; венчурний інвестор; інвестування; ризиковий капітал; інноваційні проєкти; фінансування; venture investments; venture funds; venture capital; venture investor; investing; risk capital; innovation projects; financing; 334; 330.131.7